The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2018
DOI: 10.1093/jee/toy059
|View full text |Cite
|
Sign up to set email alerts
|

Susceptibility of the Lesser Mealworm, Alphitobius diaperinus (Coleoptera: Tenebrionidae), From Broiler Farms of Southern Brazil to Insecticides

Abstract: The lesser mealworm, Alphitobius diaperinus (Panzer, 1797) (Coleoptera: Tenebrionidae), is considered the primary insect pest in broiler farms in Brazil. In this study, we characterized the susceptibility of A. diaperinus populations from broiler farms of southern Brazil to cypermethrin and chlorpyrifos. Larvae and adults of A. diaperinus were exposed to these technical insecticides diluted in acetone in residual bioassays. A geographic variation in the susceptibility of larvae and adults of A. diaperinus to b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
20
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(22 citation statements)
references
References 37 publications
1
20
0
1
Order By: Relevance
“…; Hickmann et al . ). The susceptibility level of various populations depends on the active ingredient (Tomberlin et al .…”
Section: Control Agentsmentioning
confidence: 97%
See 1 more Smart Citation
“…; Hickmann et al . ). The susceptibility level of various populations depends on the active ingredient (Tomberlin et al .…”
Section: Control Agentsmentioning
confidence: 97%
“…), tetrachlorvinphos (Singh & Johnson ), chlorpyrifos (Hickmann et al . ) and several other commonly used insecticides (Steelman ). Lambkin et al .…”
Section: Control Agentsmentioning
confidence: 99%
“…Some products are not always efficient, as they may not reach the hideouts of the insects, for instance in wall and floor crevices [ 44 ]. According to Hickmann et al [ 45 ], currently the most commonly used chemical insecticides are pyrethroids and organophosphates, which, as research has shown, leads to the growing resistance of A. diaperinus to these compounds. The resistance of the insect to fenitrothion and permethrin was observed in Great Britain back in 1996.…”
Section: Discussionmentioning
confidence: 99%
“…In turn, in Australia, the resistance of A. diaperinus against fenitrothion, deltamethrin and cyfluthrin has been experimentally confirmed, whereas in North and South America its resistance against carbaryl, methoxychlor, dichlorodiphenyltrichloroethane, cyfluthrin, permethrin, cypermethrin and chlorpyrifos has been recorded. In Brazil, a very low effectiveness of products containing cypermethrin was observed [ 45 ]. Regular identification of insecticidal susceptibility would allow manufacturers to rotate chemicals in order to reduce the insect’s resistance to insecticides in a given population [ 36 , 46 , 47 ].…”
Section: Discussionmentioning
confidence: 99%
“…An increasing number of publications have described the resistance of pest to these compounds in several countries (Tomberlin et. al., 2008;Chernaki-Leffer et al, 2011;Hickmann et al, 2018). Thus, owing to environmental pollution caused by the excessive use and misuse of agrochemicals and the requirements of health food from consumers, alternative methods must be sought.…”
Section: Introduction Smentioning
confidence: 99%